Comparative biomechanical analysis of key elements in stretched salto backward Yurchenko vault - Potop, V.; Olivia, T. (Journal of Physical Education and Sport, 2012)
The main goal of this paper is the comparative biomechanical analysis of stretched salto backward Yurchenko vault, as for the characteristics of key elements of sports technique consistent with the biomechanical indicators of these ones. For this, we considered that the biomechanical analysis of stretched salto backward Yurchenko vault would highlight the characteristics of key elements and the influence of biomechanical indicators on the correct execution of vault technique. The study was conducted from 6 to 7.07.2012 in the Sports Hall of Bucharest, during the accommodation workouts of the International Competition of Romania, the competitive period for the Olympics in London. The research aimed to analyze the biomechanics of stretched salto backward Yurchenko vault of group IV, which is a basic exercise (profile) for performing the higher difficulty vaults belonging to the same group (salto with 360º or 720º twist). The study results emphasize the comparative biomechanical analysis of key elements of stretched salto backward Yurchenko vault, applied to two senior gymnasts, members of the Romanian Olympic Team. The biomechanical analysis was performed by means of a specialized program Physics ToolKit Version 6.0, monitoring the key elements of sports technique (as per Boloban, V., 1990): start position of the body (SP), multiplication of body position (MP) and final position (FP) of the body. The biomechanical characteristics of video analysis of stretched salto backward Yurchenko vault highlights the duration of key elements, the trajectories of body segments, the height and length of flight II and the influence of biomechanical indicators (velocity and force) upon the correct execution of the vault. The characteristics of key elements of the analyzed technical structure highlight differences of girl gymnasts` anthropometric measurements while the height and length of flight depends on gymnasts` values of velocity and horizontal and vertical force. The biomechanical analysis of stretched salto backward Yurchenko vault pointed out the characteristics of key elements and the influence of biomechanical indicators upon the technical execution of the vault, which confirms the hypothesis proposed and the performances achieved in competition